2015
DOI: 10.1159/000371745
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Borderline Resectable and Locally Advanced Pancreatic Adenocarcinomas after Neoadjuvant Chemotherapy

Abstract: Objective: To report the outcomes of surgical resection of borderline resectable (BL) and locally advanced (LA) ‘unresectable' pancreatic cancer after neoadjuvant chemotherapy. Methods: A review of a prospectively maintained database for pancreatic resections was undertaken to identify patients undergoing resection for BL and LA pancreatic cancer after neoadjuvant chemotherapy between January 2007 and December 2012. Clinicopathological, surgical and survival outcomes were analyzed. Results: A total of 45 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Previous studies have demonstrated a resection rate of 25‐50% among patients with borderline resectable disease following NT, with a favorable R0 resection achieved in greater than 80% of patients . We demonstrate a similar resection rate of 55% following NT, with a R0 resection rate of 76.3%.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have demonstrated a resection rate of 25‐50% among patients with borderline resectable disease following NT, with a favorable R0 resection achieved in greater than 80% of patients . We demonstrate a similar resection rate of 55% following NT, with a R0 resection rate of 76.3%.…”
Section: Discussionsupporting
confidence: 70%
“…In the present series, the weighted average of R0 resection in arterial resection patients within the neoadjuvant subgroup was 92% compared with 50%, in the patients undergoing arterial resection without neoadjuvant chemotherapy (p < 0.001). Although neoadjuvant chemotherapy was not associated with prolonged long-term survival, our analysis suggests that it is crucial for achieving negative resection margins in this setting [12,14,59]. It has to be emphasized that in the analysis of neoadjuvant therapy, cohorts were grouped according to the predominantly administered therapy.…”
Section: Long-term Survivalmentioning
confidence: 85%
“…There are no significant changes for selection of patients for PBD in the period of the study. PBD is indicated for patients with high serum bilirubin (> 10 mg%) with high liver enzymes, renal impairment, or associated cholangitis[ 16 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%